(untitled) (Albayan Scientific Journal, 2023)
Vitamin C (VC) is a natural antioxidant found in citrus, soft fruits and leafy green vegetables and has shown protective effects against nephrotoxicity damage caused by different drugs. This study aimed to the possible protective effects of VC against renal damage induced by PCM in rats. Forty male rats were divided into five groups: Group (1) as control; receiving distilled water orally, group (2); receiving 500 mg/kg of VC. Group (3); receiving 500 mg/kg of PCM. Group (4) (protective group); receiving VC for 7 days, and then PCM for another 7 days, and group (5) treated with a combination of VC and PCM for 14 days. Renal tissue of PCM rats showed degeneration of renal corpuscles with the widening of Bowman’s space, peritubular capillary dilatation and congestion, desquamation renal tubular epithelium with damage to the brush borders of the cell and presence of debris in the tubular lumen, and pyknotic nuclei of tubular cells. However, protective rats showed the nearly normal renal structure of both cortex and medulla, but VC + PCM rats showed some modifications in kidney structures ranging. In conclusion, VC as an antioxidant can protect kidney from PCM induced tissue damage.